Problems of the Use of the Resources Internet in Professional Preparation of Master's Degree. - K.P. Osadcha (Kherson State University, 2008)
In article questions of improvement of preparation master's degree by means of resources of a network the Internet are staticized, the domestic and foreign resources the Internet focused on training master's degree are analysed; it is classified national Internet resources.